Citizenship by Investment Programs from the Perspective of International and EU Law - Weingerl, Petra; Tratnik, Matjaž (LeXonomica, 2019)
A growing number of States have been offering so-called citizenship by investment programs (CBI) or related residence by investment programs (RBI), where they offer residence and/or their nationality to foreigners willing to invest a considerable sum in their economies and/or to donate to their budget or other public funds. We focus on the CBI. Among States that offer specific CBI programs are mainly Caribbean states, but also three EU Member States, namely Bulgaria, Cyprus and Malta. The choice of an investment or donation as one of the grounds for the acquisition of the nationality of a (Member) State is in principle a legitimate choice under both international and EU law. In Section 2, we will first offer some thoughts on privileged naturalizations in State interest in general, and specifically about investment migration, before we embark on the discussion of the CBI schemes that are offered in Bulgaria, Cyprus and Malta. Section 3 explores the principle of national autonomy and its limitations both in international and EU law, with the focus on the existing CBI programs in the EU and their compatibility with international and EU law. Moreover, we will analyse the approach of the EU institutions towards such schemes.